A Japanese multi‐institutional collaborative study of antigen‐positive red blood cell (RBC) transfusions in patients with corresponding RBC antibodies. Issue 5 (2nd March 2020) - Yamada, Chiaki; Takeshita, Akihiro; Ohto, Hitoshi; Ishimaru, Ken; Kawabata, Kinuyo; Nomaguchi, Yuriko; Haraguchi, Yasue; Abe, Misao; Sobue, Koki; Takenouchi, Hiroyuki; Takadate, Junko; Kamimura, Masami; et al.
Abstract : Background and objectives: It is sometimes difficult to obtain antigen‐negative red blood cells (RBCs) for patients with antibodies against RBCs. However, the frequency and severity of the adverse reactions have not been well elucidated. Here, we conducted a multi‐institutional collaborative study to clarify the background, frequency and clinical significance of antigen‐positive RBC transfusions to patients with the respective antibodies. Materials and methods: The survey included the background of patients, antigens on RBCs transfused, total amount of antigen‐positive RBCs transfused, results from antibody screen and direct antiglobulin tests, specificity of antibodies, adverse reactions and efficacies. All antibodies were surveyed regardless of their clinical significance. Results: In all, 826 cases containing 878 antibodies were registered from 45 institutions. The main reasons for antigen‐positive RBC transfusions included 'negative by indirect antiglobulin test' (39%) and 'detection of warm autoantibodies' (25%). In 23 cases (3% of total), some adverse reactions were observed after antigen‐positive RBC transfusion, and 25 antibodies (9 of 119 clinically significant and 16 of 646 insignificant antibodies) were detected. Non‐specific warm autoantibodies were detected in 9 cases, anti‐E in 5 cases, 2 cases each of anti‐Le a, anti‐Jr a or cold alloantibodies, and 1 case each of anti‐Di b, anti‐Le b or anti‐P1. Other antibodies were detected in 2 further cases. Five (22%) of these 23 cases, who had anti‐E (3 cases) or anti‐Jr a (2 cases), experienced clinically apparent haemolysis. Conclusions: Adverse reactions, especially haemolysis, were more frequently observed in cases with clinically significant antibodies than those with clinically insignificant antibodies ( P  < 0·001).